(untitled) (Archaeologia Adriatica, 2007)
The site of Dubovo-Košno is located in a lowland area without any significant relief oscillations at ca. 83 m above sea level, not far from the Sava River, 4 km to the north of the center of Županja (Fig. 1, Fig. 2). In addition to surface finds from the late Bronze Age, the La Tène period, and the Roman period, the cultural level with settlement structures is located at a depth of 0.40 – 0.50 m. Many diverse settlement structures were discovered, both in the form of pits and above-ground elements (Fig. 5, Fig. 6). The organization of free space and communication routes represents a special group of settlement elements, but since Dubovo-Košno belongs to the type of dense Neolithic settlement in which the primary dwelling structures form the outline of the settlement, it would be difficult to speak of a clearly defined approach to organization of pathways or public areas (Fig. 6). The settlement elements of the site of Dubovo-Košno can be classified into two main groups in the general or functional sense. The first group encompasses original settlement structures, whether for dwelling, work, or auxiliary uses, while the other secondary group consists of structures created through exploitation of mineral raw materials within the area of the site. The group of primary settlement elements can be divided into four sub-groups: 1. settlement elements of general character (large settlement ditches), 2. ancillary settlement structures (remains of beam or post holes, short and deep ditches with regular plans, working or workshop pits), 3. below-ground dwelling structures (pitdwellings and sunken-floored huts), and 4. above-ground dwelling structures (houses of rectangular plan).